Experience of Guilt and Strategies for Coping with Guilt in Patients with Severe Copd: A Qualitative Interview Study. Issue 2 (June 2014) - Strang, Susann; Farrell, Mary; Larsson, Lars-Olof; Sjöstrand, Charlotte; Gunnarsson, Anna; Ekberg-Jansson, Ann; Strang, Peter
Guilt is associated with an increased level of mood disturbance and a poorer quality of life. The aim of this study was to explore how patients with severe COPD view and experience guilt and the ways in which they cope with this guilt. A total of 31 COPD patients were interviewed about their perceptions and experiences of guilt. Qualitative content analysis was used to examine the interviews. In the descriptive (manifest) analysis, the categories "not feeling personal guilt" and "experiencing guilt" emerged; in the interpretative (latent) analysis, various strategies for dealing with guilt were identified — for example, acceptance or blaming others. Relatively few patients reported that they felt guilt on a conscious level, but those who did expressed anguish, and remorse before God; some felt blamed by others. It is important that healthcare providers acknowledge the guilt that their patients express, since guilt may have adverse effects on the patients' overall health.